Measurement of the refractive index of solutions based on digital holographic microscopy. (15th December 2017) - Huang, Sujuan; Wang, Weiping; Zeng, Junzhang; Yan, Cheng; Lin, Yunyi; Wang, Tingyun
Abstract: A new approach for the refractive index (RI) measurement of solutions is proposed based on digital holographic microscopy. The experimental system consists of a modified Mach–Zehnder interferometer and related lab-developed analysis software. The high quality digital hologram of the tested solution is obtained by the real-time analysis software, which is firstly encapsulated into a capillary tube, and then the capillary tube is inserted in a matching fluid. An angular spectrum algorithm is adopted to extract the phase distribution from the hologram recorded by a CCD. Based on a capillary multi-layer calculation model, the RI of the tested solution is obtained at high accuracy. The results of transparent glycerol solution measured by the proposed method are more accurate than those measured by the Abbe refractometer. We also measure the RI of translucent magnetic fluid, which is not suitable to be measured by the Abbe refractometer. The relationship between the RI and the concentration of magnetic fluid is experimentally studied, and the results show that the RI is linearly related to the concentration of dilute magnetic fluid.